Knowledge from Falsehood: An Experimental Study. (7th June 2019) - Turri, John
Abstract: Philosophers have debated whether it is possible to knowledgeably infer a conclusion from a false premise. For example, if a fan believes that the actress's dress is blue, but the dress is actually green, can the fan knowledgeably infer "the dress is not red" from "the dress is blue?" One aspect of this debate concerns what the intuitively correct verdict is about specific cases such as this. Here, I report a simple behavioral experiment that helps answer this question. The main finding is that people attribute knowledge in cases where a true conclusion is inferred from a false premise. People did this despite judging that the premise was false and unknown. People also viewed the agent as inferring the conclusion from the premise. In closely matched conditions where the conclusion was false, people did not attribute knowledge of the conclusion. These results support the view that the ordinary knowledge concept includes in its extension cases of knowledge inferred from false premises.